Lipid production by microalga Scenedesmus sp. AARL G022 in the cultivation with effluent from chicken manure biogas plant - Duangjan K. (2017)
© 2016 Balaban Desalination Publications. All rights reserved. Microalgae are potential organisms in biooil production and they can accumulate higher lipid content than other oil plants. However, one of the major problems in algal oil production is its high cost. The aim of this study was to culture Scenedesmus sp. AARL G022 with the effluent from chicken manure biogas plant and evaluate its lipid accumulation. The effluent from the biogas plant was used directly or filtered through the water purifier at 6, 12, 25, 50, and 100% concentrations without additional nutrient supplementation. The highest level of growth was obtained when the microalga was cultivated with 12–25% of the non-filtered effluent. The highest level of biomass production involving Scenedesmus sp. AARL G022 was selected in order to upscale to a culture volume of 20 L using 12–25% of the non-filtered effluent. It was found that Scenedesmus sp. AARL G022 revealed the highest levels of growth as was observed using 25% of non-filtered effluent with chlorophyll a and a maximum biomass reading of 3,055.34 ± 331.86 μg mL −1 and 0.54 ± 0.06 g L −1 , respectively, and a maximum lipid reading of 44.50 ± 4.35 mg L −1 . Fatty acid profiles showed that palmitic acid (C16:0) and linoleic acid (C18:2) were the major fatty acids. This study will be useful for the purposes of increasing algal biomass and lipid production, as well as in the reduction of nutrient costs and the amounts of discharged wastewater.